Micro- and nano- techniques of controlling microhardness of photopolymer composite materials for use in stomatology - Hotra, Zenon; Makeev, Valentyn; Mykyevych, Nataliya (Видавництво Львівської політехніки, 2012)
Methods of investigation into microhardness of photopolymer composite materials used in stomatology are considered. Results of using MHT and NHT methods are compared.
Keywords: microhardness; photopolymer materials; MHT; NHT; stomatology